Efektivitas Pembelajaran Mufradat dengan Menggunakan Metode Musyabahah - Syarifuddin; Nadiyah, Jamilatun; Syaifullah (Mu'allim, 2025)
This musyabahah method is still not familiar and has not been used often in learning mufradat, that's why researchers are interested in conducting experimental research on this musyabahah method. The application and effectiveness of the Mushabaha method in learning Arabic Mufradat in Madrasah Diniyah Darut Taqwa Ula Purwosari Pasuruan is the aim of this research. This research is a type of experimental quantitative research. Group pretest-posttest plan is the method used. The sample of this study was 29 students of class 2 O1 with data collection techniques in the form of observation, tests and documentation. The data analysis technique was carried out by testing the validity, reliability, normality test and t test. The results of this study explain that the application of mufradat learning using the musyabahah method is that researchers explain some of the findings of mufradat in Arabic books that have musyabahah elements in Indonesian. The results of the effectiveness are significant with the results of hypothesis testing showing that tcount is greater than ttable, namely 6.594 > 2.042 and Sig. (2 tailed) = 0.000 < 0.05